Governamentalidade e Educação: discursos e vivências no processo de subjetivação de jovens em uma Escola Estadual de Educação Profissional cearense a partir do modelo escola-empresa - Vasconcelos, Francisco Ullissis Paixão e (2020)
This study takes as an element of problematization the movements of capturing education by the business model that reconfigures the way schools operate, and is configured as a subjectification device, in the scenario of the State Schools of Professional Education (EEEP) of Ceará, of young students. Amidst the configurations of the current society and the ever inventive transformations with regard to neoliberal aesthetics, we see a model of entrepreneurship in education emerging, making it more and more managed and naturalizing concepts specific of the market, as being, now, belonging to the educational context , such as: business, profit, protagonism and entrepreneurship. This agency of education through neoliberal discursive arrangements engender certain “modus operandi” of a governmentality that, gradually, distances itself from the republican ideals of education, configuring itself in the name of neoliberal principles of interest such as: competition, meritocracy and self-management , including with regard to accountability for their employability processes. In this context, this Thesis discusses, in a more central way, two discursive modalities present in the context of Ceará's EEEP: the discourses about Youth Protagonism and the Young Entrepreneur. As this study makes movements that pay attention to the production process of bodies and subjectivities of young students through practices and discourses that guide the experiences of the self, it falls within the scope of studies in Psychology, seen here from a Foucaultian framework. This work, which we have placed on the list of qualitative research, was developed from two movements: an archeogenealogic, and another cartographic. In the archeogenealogical path, it was possible to historicize the paths and conditions of possibility that allowed business discourses to get closer, so naturally, to education. And in the cartographic we try to build the possible maps, thought as provisional effects, of the subjectivation processes and the resistance of the young people in the context of the EEEP of Ceará. The central question that guided this research was: how does the entrepreneurship of education operate as a subjectification device for young people in the scenario of the State Schools of Professional Education in Ceará? And, based on it, our general objective was: to analyze the modes of operation of the business model adapted for education, and its effects as a subjectification device for young students, in the scenario of a professional school in Ceará. At the end of this study, what remains for us is that the movements woven in this scenario are consistent with the articulations to foster an experience of self, where the first and real undertaking will be to undertake, with a reflective verb that guides the experience of young people with themselves, from a neoliberal governmentality.